2021
DOI: 10.1101/2021.03.30.437707
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The innate immune kinase TBK1 directly increases mTORC2 activity and downstream signaling to Akt

Abstract: TBK1 (TANK-binding kinase 1) responds to microbial pathogens to initiate cellular responses critical for host innate immune defense. We found previously that TBK1 phosphorylates mTOR (mechanistic target of rapamycin) (on S2159) to increase mTOR complex 1 (mTORC1) activity and signaling in response to the growth factor EGF and the viral dsRNA mimetic poly(I:C). mTORC1 and the less well studied mTORC2 respond to diverse cues to control cellular metabolism, proliferation, and survival. Here we demonstrate that TB… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 78 publications
(171 reference statements)
0
5
0
Order By: Relevance
“…TBK1 activity is increased by phosphorylation of S172 in its activation J o u r n a l P r e -p r o o f loop in response to pathogens in the innate immunity pathway. In contrast, Tooley et al found that EGF stimulation did not enhance S172 phosphorylation, supporting that it is the basal activity of TBK1 that is important for mTORC2 signaling downstream of growth factors (6). However, when RAW264.7 macrophages and primary bone marrow-derived macrophages were stimulated with the double-stranded RNA mimetic poly(I:C), which induces TBK1-S172 phosphorylation, TBK1 and mTOR-S2159 were also found to be required for mTORC2-dependent phosphorylation of Akt-S473.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 97%
See 4 more Smart Citations
“…TBK1 activity is increased by phosphorylation of S172 in its activation J o u r n a l P r e -p r o o f loop in response to pathogens in the innate immunity pathway. In contrast, Tooley et al found that EGF stimulation did not enhance S172 phosphorylation, supporting that it is the basal activity of TBK1 that is important for mTORC2 signaling downstream of growth factors (6). However, when RAW264.7 macrophages and primary bone marrow-derived macrophages were stimulated with the double-stranded RNA mimetic poly(I:C), which induces TBK1-S172 phosphorylation, TBK1 and mTOR-S2159 were also found to be required for mTORC2-dependent phosphorylation of Akt-S473.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 97%
“…Spleen tissue isolated from Mtor A/A mice showed diminished Akt-S473 phosphorylation. Therefore, the authors conclude that under both basal and activated states, the activation of Akt by TBK1 is mediated through mTORC2 (Figure 1) (6).…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 97%
See 3 more Smart Citations